Performing urological inpatient procedures as same-day procedures during the COVID pandemic: A retrospective feasibility study - Siron, Nicolas; Assad, Anis; Ouirzanne, Mona; Lafontaine, Marie-Lyssa; Zorn, Kevin C.; Lattouf, Jean-Baptiste; Meskawi, Malek; Duceppe , Emmanuelle; Bhojani, Naeem (Canadian Urological Association Journal, 2023)
INTRODUCTION: In line with Canadian provincial directives due to the COVID-19 pandemic, certain elective urologic surgical cases that are normally performed as inpatient procedures were performed as same-day discharge procedures to reduce hospitalization and the usage of scarce healthcare resources. Since the pandemic, we began performing laser enucleation of the prostate (LEP), robotic-assisted radical prostatectomy (RARP), and percutaneous nephrolithotomy (PCNL) as outpatient surgeries. This was supported by recent evidence demonstrating the safety and feasibility of performing these minimally invasive surgeries as same-day procedures. As such, we sought to retrospectively evaluate the clinical outcomes and safety during the COVID-19 era at our institution for same-day discharge LEP, RARP, and PCNL procedures. METHODS: All patients operated for LEP, RARP, or PCNL between May 2020 and March 2022 at two academic institutions were included. Surgeries were classified as planned sameday discharge or inpatient surgery. Same-day discharge patients were compared to inpatients for each procedure type. This comparison assessed the occurrence of same-day failure, postoperative complications, and re-admission rates at 30 days. This study was approved by the scientific ethics committee of the Centre de Recherche de l’Université de Montréal (CRCHUM). RESULTS: A total of 413 subjects were included in this study. Among LEP patients (n=169), 104 (62%) were identified as same-day procedures and 65 (38%) were inpatient. Among RARP patients (n=194), 46 (24%) were identified as same-day procedures and 148 (76%) inpatient. Among PCNL patients (n=50), 38 (76%) were identified as same-day procedures and 12 (24%) were inpatient. Of the patients who underwent planned same-day LEP, RARP, and PCNL, 77.9%, 73.9%, and 71.1% were successfully discharged home, respectively. Patients who underwent LEP as inpatients had a higher incidence of overall postoperative complications compared to same-day LEP (23.1% vs. 8.7%, p=0.017). The rates of 30-day emergency department (ED) visits and hospital re-admission were similar between inpatient and same-day LEP (9.2% vs. 3.8%, p=0.27; and 4.6% vs. 1.0%, p=0.32, respectively). Inpatient RARP, however, was associated with more 30-day ED visits compared to same-day procedures (17.4% vs. 4.1%, p<0.01). No statistically significant differences were found for postoperative complications (15.2% vs. 6.1%, p=0.097) and re-admission rates (1.4% vs. 4.3%, p=0.51). There were no significant differences on overall postoperative complications, 30-day ED visits, and re-admission rates in inpatient vs. same-day PCNL. CONCLUSIONS: Our results suggest that same-day discharge for LEP, RARP, and PCNL is safe and feasible in select patients, with an acceptable complication rate. These results should be validated in a larger, prospective clinical trial comparing same-day and inpatient procedures.